2016
DOI: 10.1128/jvi.00155-16
|View full text |Cite
|
Sign up to set email alerts
|

Functional Transplant of a Dengue Virus Serotype 3 (DENV3)-Specific Human Monoclonal Antibody Epitope into DENV1

Abstract: The four dengue virus (DENV) serotypes, DENV1 through 4, are endemic throughout tropical and subtropical regions of the world. While first infection confers long-term protective immunity against viruses of the infecting serotype, a second infection with virus of a different serotype carries a greater risk of severe dengue disease, including dengue hemorrhagic fever and dengue shock syndrome. Recent studies demonstrate that humans exposed to DENV infections develop neutralizing antibodies that bind to quaternar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 43 publications
0
50
0
Order By: Relevance
“…The binding of these antibodies was not decreased by residues identified as epitopes for the group A, B, or C antibodies. We note in particular that binding of the quaternary antibody 5J7 (27) lies on the E protein surface at the DI-DII interface close to the mutations identified on the underside of the E protein for group C antibody 7E-H1L1. However, binding by 5J7 was unaffected by any of these mutations on the underside, further suggesting that the epitope residues identified here for group A, B, C, and D antibodies do not perturb the global structure of the E protein.…”
Section: Resultsmentioning
confidence: 55%
“…The binding of these antibodies was not decreased by residues identified as epitopes for the group A, B, or C antibodies. We note in particular that binding of the quaternary antibody 5J7 (27) lies on the E protein surface at the DI-DII interface close to the mutations identified on the underside of the E protein for group C antibody 7E-H1L1. However, binding by 5J7 was unaffected by any of these mutations on the underside, further suggesting that the epitope residues identified here for group A, B, C, and D antibodies do not perturb the global structure of the E protein.…”
Section: Resultsmentioning
confidence: 55%
“…Human DENV1, DENV2, and DENV3 type-specific neutralizing antibodies often bind to quaternary structure epitopes centered on the EDI/II hinge (17-19, 21, 38) and/or the EDIII region (2,20,21,39,40). Recently, we demonstrated that it is possible to recover recombinant chimeric DENVs displaying E protein domains or epitopes from viruses of two different serotypes (38,39). We used a rDENV4 strain with a mutated EDI/II hinge region and EDII region (rDENV4/3) to map the binding sites of hMAbs D4-126 and D4-131 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…75,9295 These antibodies bind multiple sites on the E protein, including regions of EDIII, the fusion loop, and the hinge of EDI/II. 93 New tools are becoming available to dissect the repertoire of polyclonal sera, using depletion methods and epitope-transplanted recombinant viruses; 49,96,97 applying these to better understand the antibody response and potential immune correlates in DENV natural infections and vaccines is an area of active research.…”
Section: Immune Correlates Of Protection and Riskmentioning
confidence: 99%
“…144 Novel approaches being explored include “scaffolding” complex epitopes, such as the cross-neutralizing EDE epitope; bivalent vaccines that present two potent neutralizing type-specific epitopes simultaneously; and recombinant viruses on which epitopes recognized by enhancing antibodies are “masked”. 97,145,146 …”
Section: Dengue Vaccinesmentioning
confidence: 99%